A Portuguese East Indiaman from the 1502–1503 Fleet of Vasco da Gama off Al Hallaniyah Island, Oman: an interim report. (14th March 2016) - Mearns, David L.; Parham, David; Frohlich, Bruno
Abstract : Two Portuguese naus from Vasco da Gama's second voyage to India, left behind to disrupt maritime trade between India and the Red Sea, were wrecked in May 1503 off the north‐eastern coast of Al Hallaniyah Island, Oman. The ships, Esmeralda and São Pedro, had been commanded by da Gama's maternal uncles, Vicente and Brás Sodré, respectively. A detailed study and scientific analysis of an artefact assemblage recovered during archaeological excavations conducted in Al Hallaniyah in 2013 and 2014 confirms the location of an early 16th‐century Portuguese wreck‐site, initially discovered in 1998. Esmeralda is proposed as the probable source of the remaining, un‐salved wreckage.